Effect of Vibratory Finishing on the Vibration Characteristic of Gear - Qiao Jinwei; Wu Zhifei; Wang Tie; Zhang Ruiliang; Wang Daoyong (Jixie chuandong, 2017)
The vibratory finishing process is applied to spur gear processing of surface finishing,and the surface roughness is reduced. The vibration performance contrast experiment of test gear is carried out in the closed power flow test bench,the results indicate that vibration and noise are reduced under three kinds of conditions,thus the vibratory finishing has an obvious effect of vibration reduction,and it has a certain value of reference and application.